Training toolkit resources for traini ng coordinators, curriculum developers and trainers - International Training and Education Center on HIV. ([s.l] : I-TECH, 2006)
This Toolkit is a collection of original and revised resources for d eveloping, delivering, and evaluating training on HIV-related topics an d skills for healthcare providers
Insert the CD into your computer; If you're accessing the Toolkit fr om Windows:* Open "My Computer" on the desktop, then open the CD.*Doubl e click on "toolkit" or "toolkit.html".
"October 2005"
Systems requirements: Software capable of displaying a PDF is requir ed for viewing or printing the document.
Keywords: HIV infections -- Prevention; AIDS (Disease) -- Prevention